2014
DOI: 10.12681/mms.609
|View full text |Cite
|
Sign up to set email alerts
|

Prey utilisation and trophic overlap between the non native mosquitofish and a native fish in two Mediterranean rivers

Abstract: Non native freshwater fish species have been long implicated in the decline of native Mediterranean ichthyofauna, through hybridization, disease transmission, competition for food and habitat, predation and/or ecosystem alteration; our knowledge, however, on the underlying mechanisms of these ecological impacts remains very limited. To explore the potential for trophic competition between the widespread Eastern mosquitofish Gambusia holbrooki and its co-occurring native toothcarp Valencia letourneuxi we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…More recently, Kalogianni et al . () demonstrated that G. holbrooki can exert trophic competition and larvae predation on native zournas Valencia letourneuxi (Sauvage). Although potential impacts in Greece are not proven (being either descriptive or speculative) for C. carpio , C. auratus (Leonardos et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Kalogianni et al . () demonstrated that G. holbrooki can exert trophic competition and larvae predation on native zournas Valencia letourneuxi (Sauvage). Although potential impacts in Greece are not proven (being either descriptive or speculative) for C. carpio , C. auratus (Leonardos et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Kalogianni et al . ), but the lack of evidence does not necessarily imply the absence of an adverse impact. This is particularly evident in the case of the underestimated impact of non‐native disease agents on native freshwater fishes, where available data are largely based on a few farmed species (Athanassopoulou & Ragias ; Athanassopoulou et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are few studies assessing the presumed negative impacts of the mosquitofish on the two Greek Valencia species or the mechanisms underlying them. In a recent comparative dietary study, evidence has been presented that the underlying mechanism of the putative negative impacts of the mosquitofish on the declining Corfu Valencia is mainly trophic competition, regulated by resource variability, though there is also evidence of larvae predation by the mosquitofish (Kalogianni et al, 2014). More experimental as well as in situ studies are, however, required in order to determine the effects of the mosquitofish/native species' agonistic interactions and/ or trophic competition on the abundance, condition and reproduction of native fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive species are often superior competitors in relation to the evolutionary isolated native species populations (Mills, Rader, & Belk, 2004;Townsend, 1996), and they have broader environmental tolerances, being thus able to thrive in degraded habitats (Courtenay & Meffe, 1989;Kennard et al, 2005). Their negative impacts on native species include predation, trophic competition, behavioural interference, hybridization, spread of novel parasites and diseases, alteration of food webs and modification of biochemical cycles (Arthington & Lloyd, 1989;Mills et al, 2004;Keller & Brown, 2008;Kalogianni, Giakoumi, Andriopoulou, & Chatzinikolaou, 2014; for reviews, see Leunda, 2010;Cucherousset & Olden, 2011). However, the invasion process contains a series of stages, from introduction, survival and reproduction to dispersal, with species having to overcome barriers to reach the next step, with differing invasion success (Blackburn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%